2013
DOI: 10.1111/codi.12200
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to Enhanced Recovery After Surgery and length of stay after colonic resection

Abstract: Aim The Enhanced Recovery After Surgery (ERAS) programme is a multimodal approach to improve peri--operative care in colon surgery. The aim of this study was to report on the adherence to and outcomes of ERAS in the first years after implementation. Multivariate analysis showed that age, laparoscopic surgery, removal of nasogastric tube before extubation, mobilization within 24 h after surgery, starting nonsteroidal anti-inflammatory drugs at day 1 and removal of thoracic epidural analgesia at day 2 were indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
1
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(54 citation statements)
references
References 21 publications
4
48
1
1
Order By: Relevance
“…Comparing our present study with other studies could be difficult because of the difference in the items as well as due to the difference in the number of items, which ranged from 4 to 14 in a systematic review [10] . The reported compliance rates compare favorably with those of the previous published studies, especially for the pre-and perioperative period [8,11] . In spite of the potential confounding effect of postoperative recovery and the occurrence of complications on compliance to postoperative items [8] , postoperative items were also reported and analyzed.…”
Section: Discussionsupporting
confidence: 81%
“…Comparing our present study with other studies could be difficult because of the difference in the items as well as due to the difference in the number of items, which ranged from 4 to 14 in a systematic review [10] . The reported compliance rates compare favorably with those of the previous published studies, especially for the pre-and perioperative period [8,11] . In spite of the potential confounding effect of postoperative recovery and the occurrence of complications on compliance to postoperative items [8] , postoperative items were also reported and analyzed.…”
Section: Discussionsupporting
confidence: 81%
“…The inability to achieve high compliance is commonly cited as a reason why quality improvement programs fail. 6,18,37,38 To avoid this potential pitfall, elements of the ERP and SSIB have been protocolized and integrated into physician order sets, which has facilitated reliable delivery of these programs. Additionally, CRS leadership meets frequently with members of the multidisciplinary team that enacts the components of these programs in order to reinforce program objectives, identify problem areas, and improve program coordination.…”
Section: Discussionmentioning
confidence: 99%
“…It was noted, however, that there was a variation in the percentage of laparoscopic resections over the 8 years, which may have influenced results on LOSH. Cakir et al [24] also reported that strict adherence to the ERAS protocol resulted in lower LOSH and improved outcomes in colon surgery for malignancy. In colorectal laparoscopic surgery, Pisarska et al [25] reported consistent findings by showing that improvement of protocol compliance leads to better treatment results and convalescence parameters, even when groups with high and very-high compliance rate are compared.…”
Section: Outcomes Colonic Surgerymentioning
confidence: 99%